Teratogenic Test of Brotowali Stem Extract (Tinospora Crispa) And Temulawak Rhizome Extract (Curcuma Xanthorrhiza) On Fetus Mencit Putih (Mus musculus) - Bagas Ardiyantoro; Ason Merari P; Mardiyono Mardiyono (Green Publisher Indonesia, 2024)
The stem of Brotowali and the rhizome of Temulawak are among the ingredients used in the production of traditional herbal medicine, specifically Brotowali and Temulawak herbal concoctions. These herbal mixtures are also consumed by pregnant women. The extracts from Brotowali stem and Temulawak rhizome contain bioactive antioxidants of the flavonoid group. Flavonoid compounds can inhibit the activities of phosphodiesterase enzymes that hydrolyze cAMP, and an elevated concentration of cAMP can impede growth acceleration. The aim of this research is to determine the teratogenic effects on white mouse fetuses after the administration of Brotowali stem and Temulawak rhizome extracts. The study involved 49 white mice (Mus musculus) divided into 5 groups. The first test group was given 0.5% Na CMC and used as the negative control, the second test group was injected with intravenous Cyclophosphamide at 50 mg/kg BW for the positive control. The groups included EB Dose 1120, ET Dose 1120, Dose 1 EBT 2:1, Dose 2 EBT 1:2, and Dose 3 EBT 1:1. Brotowali stem and Temulawak rhizome extracts were administered during the organogenesis period, and on the 18th day, the mice were subjected to laparotomy to collect the fetuses. Biometric, gross morphological, and skeletal abnormality observations were conducted to assess the effects of Brotowali stem and Temulawak rhizome extract administration. The research results indicate that Brotowali stem and Temulawak rhizome extracts have the potential to cause teratogenic effects, particularly at Dose 3 EBT 1:1.